Water Supply Facility Damage and Water Resource Operation at Disaster Base Hospitals in Miyagi Prefecture in the Wake of the Great East Japan Earthquake. Issue 2 (9th February 2015) - Matsumura, Takashi; Osaki, Shizuka; Kudo, Daisuke; Furukawa, Hajime; Nakagawa, Atsuhiro; Abe, Yoshiko; Yamanouchi, Satoshi; Egawa, Shinichi; Tominaga, Teiji; Kushimoto, Shigeki
Abstract: Introduction: The aim of this study was to shed light on damage to water supply facilities and the state of water resource operation at disaster base hospitals in Miyagi Prefecture (Japan) in the wake of the Great East Japan Earthquake (2011), in order to identify issues concerning the operational continuity of hospitals in the event of a disaster. Methods: In addition to interview and written questionnaire surveys to 14 disaster base hospitals in Miyagi Prefecture, a number of key elements relating to the damage done to water supply facilities and the operation of water resources were identified from the chronological record of events following the Great East Japan Earthquake. Results: Nine of the 14 hospitals experienced cuts to their water supplies, with a median value of three days (range = one to 20 days) for service recovery time. The hospitals that could utilize well water during the time that water supply was interrupted were able to obtain water in quantities similar to their normal volumes. Hospitals that could not use well water during the period of interruption, and hospitals whose water supply facilities were damaged, experienced significant disruption to dialysis, sterilization equipment, meal services, sanitation, and outpatient care services, though the extent of disruption varied considerably among hospitals. None of the hospitals had determined the amount of water used for different purposes during normal service or formulated a plan for allocation of limited water in the event of a disaster. Conclusion: The present survey showed that it is possible to minimize the disruption and reduction of hospital functions in the event of a disaster by proper maintenance of water supply facilities and by ensuring alternative water resources, such as well water. It is also clear that it is desirable to conclude water supply agreements and formulate strategic water allocation plans in preparation for the eventuality of a long-term interruption to water services. T Matsumura, S Osaki, D Kudo, H Furukawa, A Nakagawa, Y Abe, S Yamanouchi, S Egawa, T Tominaga, S Kushimoto .Water supply facility damage and water resource operation at disaster base hospitals in Miyagi Prefecture in the wake of the Great East Japan Earthquake .Prehosp Disaster Med .2015 ;30 (2 ):1 -5 .